1979
DOI: 10.1002/1097-4679(197907)35:3<680::aid-jclp2270350337>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Sex of client as a factor in preference for an approach to counseling

Abstract: In a reversed order, 90 Ss, from a general psychology course, in two groups of equal size, viewed two audiovisual tapes of a simulated first counseling session. The same counselor, same client, and same presenting concern of a vocational‐educational nature were portrayed as representative of a client‐centered and a behavioral approach to counseling. The Ss were asked to identify which film they preferred and why. A chi square analysis showed no difference between males and females. However, there was a statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Previously cited research (Cashen, 1979a(Cashen, , 1979b(Cashen, , 1980Stuehm, Cashen, & Johnson, 1977) has shown a preference for this approach when the concern was in the vocational-educational realm. It was logical to assume that this approach would also be preferred when the concern was in the personal domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously cited research (Cashen, 1979a(Cashen, , 1979b(Cashen, , 1980Stuehm, Cashen, & Johnson, 1977) has shown a preference for this approach when the concern was in the vocational-educational realm. It was logical to assume that this approach would also be preferred when the concern was in the personal domain.…”
Section: Discussionmentioning
confidence: 99%
“…Stuehm, Cashen, and Johnson (1977) found that both internally and externally oriented students preferred a behavioral approach as opposed to a client-centered one, as do those in the general population (Cashen, 1979a). Also, there appeared to be no sex differences, as both sexes prefer a behavioral approach (Cashen, 1979b).…”
mentioning
confidence: 95%
“…Other writers have looked at preferences for different help sources as a function of the type of problem for which help might be sought (Cook et al, 1984;Tinsley, de St. Aubin, & Brown, 1982;Tryon, 1980). Preferences for counselors' response styles or theoretical approaches have also been Identified in the literature (Cashen, 1979;Holen & Kinsey, 1975;Sobel, 1979).…”
Section: Descriptive Studiesmentioning
confidence: 99%
“…These include: a) consultant modeling of treatment techniques for consultees or interacting with consultees in the classroom, b) consultant's physical location in relation to the consultee and contact with the consultee, c) consultant warmth and concern for the client and consultee Rogers, 1957), d) expertise and status of the consultant (Goldstein, 1974), and e) the structure and directiveness of the consultant (Cashen, 1979;.…”
Section: The Consultation Relationshipmentioning
confidence: 99%